2009
DOI: 10.1111/j.1365-2133.2009.09536.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of papulopustular eruptions caused by cetuximab treatment shows altered differentiation markers and increases in inflammatory cytokines

Abstract: The early inflammatory events (IL-1alpha and TNF-alpha expression) seen, and the lack of pEGFR in perilesional follicles, indicate that inflammatory events induced by EGFR inhibition may initiate papulopustular eruptions along with the altered differentiations. The decrease of filaggrin may contribute to the pathogenesis of the xerosis caused by cetuximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
0
21
0
2
Order By: Relevance
“…Thus, the role of tumor necrosis factor-α (TNF-α) and interleukin-1 (IL-1) in the development of EGFR inhibitor-associated skin rash was shown and a possible therapeutic role for anti-TNF agents was suggested [35]. It has previously been described that the EGFR-specific antibody cetuximab induced papulopustular eruptions and induced production of IL-1 and TNF-α [36]. Cetuximab and zalutumumab employ similar mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the role of tumor necrosis factor-α (TNF-α) and interleukin-1 (IL-1) in the development of EGFR inhibitor-associated skin rash was shown and a possible therapeutic role for anti-TNF agents was suggested [35]. It has previously been described that the EGFR-specific antibody cetuximab induced papulopustular eruptions and induced production of IL-1 and TNF-α [36]. Cetuximab and zalutumumab employ similar mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR belongs to a group of membrane bound receptor tyrosine kinases with extracellular ligand-binding domain and cytoplasmic domain possessing intrinsic protein kinase activity (1,25,26,31). EGFR is expressed through all layers of human epidermis with the strongest presence in the basal layer of epidermal keratinocytes (2,10,(24)(25)(26)(27).…”
mentioning
confidence: 99%
“…A number of publications from our group (26,27,29) has shown that EGFR controls expression of inflammatory chemokines (CXCL8/interleukin 8 , CCL2/monocyte chemotactic protein-1 [MCP-1], CXCL10/interferon gamma-induced protein of 10 kDa [IP-10], CCL5/regulated upon activation, normal T-cell expressed [RANTES]) and granulocyte-macrophage growth factor in normal human keratinocytes, and EGFR impairment accounts for overexpression of distinct chemokines in the skin affected by chronic inflammation. It has also been suggested that adverse skin reactions (inflammation and hyperkeratosis) to anti-EGFR antitumor therapies may be a consequence of the impaired control of suppressed EGFR over keratinocyte proliferation and their inflammatory responses (10,25,29,30,46). Although EGFR involvement in cancer cell proliferation and their chemo-resistance attracts major attention (24), there is substantial evidence that EGFR system is essential to guide keratinocyte proliferation, migration, and survival to maintain normal skin homeostasis or restore epidermal integrity after wounding.…”
mentioning
confidence: 99%
“…Those eruptions are characterized by an intensive infiltration of neutrophils into follicles. 4 In our case, an abrupt epidermal necrosis with a scarce infiltration of neutrophils under the ulceration may imply causes other than an activation of neutrophils although an infiltration of neutrophils into the epidermis around the ulceration was found. 5 It is also intriguing in terms of clinical manifestations that multiple purpuras up to 2-3 mm in diameter, which were epidermal necrosis histopathologically, were scattered on her trunk and limbs.…”
mentioning
confidence: 92%